Study of Drug-drug Interactions in the Medication Charts in Medicine Wards at a Tertiary Care Hospital, Bangalore - O.D, Jimmy; R.H, Shobha Rani; R, Indira; S, Ramjan (Indian Journal of Pharmacy Practice)
Introduction: Drug-drug interactions (DDIs) can occur when two or more medications are simultaneously administered, where one medication increases or decreases the effectiveness of the other. There are three possible outcomes when drug-drug interactions occur; one drug may intensify the effects of the other, one drug may reduce the effects of the other and the combination may produce a new response which is not seen when either of the drugs is given alone. Objective: This prospective study aimed to evaluate drug-drug interactions in the medication charts of the patients. Data of all patients admitted to MICU and Female Medical Ward was collected and subjected to drug-drug interaction analysis using ® drug information resources such as “Thomson Reuters MICROMEDEX 2.0 DRUGDEX anddrugs.com. Results: From among the 230 cases collected, 120 (52.17%)cases were identified with 330 DDIs out of which 10 (3.03%) were clinically observed and the rest 320 were potential DDIs. Majority (80.86%) of the potential DDIs were of pharmaco dynamic in nature. It was observed that out of 330 DDIs identified, 82 (24.85%) were major, 176 (53.33%) were moderate and 72 (21.82%) were minor in severity. Atleast one potential DDI was observed in 35% of the prescriptions. Conclusion: DDIs may not appear to cause a serious problem to the health of the patients and process of drug therapy but clinical investigations are required to know the actual consequence of the DDIs.
Keywords: Drug-drug interactions; medication charts; adverse drug reactions